Draft Annual Plan 1978-79 (In 4 Volumes) Vol. III Haryana State - Planning Commission (Planning Commission, 1978)
The Third conference of State Ministers of Irrigation held on 8th and 9th November 1977 recommended that the development of Irrigation in the five year starting 1978-79 should be considerably accelerated and the outlays may be 2 to 2 1/2 times in outlays for V Plan. Proposals submitted are in keeping with the recommendations of the Conference.
Planning Department, Government of Haryana